Influence of Work Flexibility and Quality of Work Life on Job Loyalty among Generation Z Employees - abid habibi; Diin Fitri (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2025)
This study aim to analyse the influence of work flexibility, and quality of work life on job loyalty among generation Z employee in South Jakarta. This research uses a quantitive approach, with a samle of 154 respondents collected through questionnaires. Data analysis in this study uses the Structural Equation Model Partial Least Square (SEM PLS) method with the SMART PLS software version 4.0. The sampling technique used in this research is convenience sampling. Based on the analysis result, the study shows that work flexibility has a positive effect on job loyalty amaong generation Z. the analysis shows a T-statistic value of 14.228, and this is supported by a P-Value of 0.000, which is less than 0.0. Furthermore, the second hypothesis indicates that quality of work life also has significant influence on job loyalty, proven by a T-statistic value of 6.431 and a P-value of 0.000, which is also below 0.05. Keywords : Work Flexibility, Quality of Work Life, Job Loyalty.